2019
DOI: 10.4236/jacen.2019.83014
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Fortification Study of Some Common African Vegetables

Abstract: Iodine Deficiency Diseases (IDDs) occupy important positions in the health problems of developing countries. Salt Iodisation has been the common approach to solving these problems. However, apart from the problems of lack of compliance by salt manufacturers, and inculturation of the consumers, health conditions aggravated by high salt intake by humans have become increasingly relevant. These problems can be eliminated if the commonly produced and consumed plants are fortified with Iodine. The prospects are in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…One each of the plants was left uninoculated (control). The iodine content was evaluated using Dry Alkaline Ash Method as described by Anarado et al, [32], was used after 14 days. This was done by adding 0.5 g of each of the samples into a nickel crucible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One each of the plants was left uninoculated (control). The iodine content was evaluated using Dry Alkaline Ash Method as described by Anarado et al, [32], was used after 14 days. This was done by adding 0.5 g of each of the samples into a nickel crucible.…”
Section: Methodsmentioning
confidence: 99%
“…Ujowundu et al, 2009 studied Iodine fortification of Selected Plants Using Potassium Iodide and found that iodine biofortification of Telfairia occidentalis, Talinium trangulare and Zea mays if properly harnessed, may improve the iodine content of plants [31]. "In our previous work, we also studied Iodine Fortification Study of Some Common African Vegetables using potassium iodide and potassium iodate and found out that Murraya koenigii, Ocimum gratissimum, Solanum nigrum, Zingiber officinale can be used in iodine biofortification using KI and KIO3 at concentration < 0.5 M" [32]. Caffagni et al, 2011 studied the iodine fortification of Hordeum vulgare , Zea mays , Nicotiana tabacum , Solanum tuberosum and Solanum lycopersicum using potassium iodide and potassium iodate and reported that Solanum tuberosum and Solanum lycopersicum were shown to be good targets for a fortificationrate study among the species screened [33].…”
Section: Introductionmentioning
confidence: 99%
“…The fortification of pumpkins may also constitute an attractive alternative source of iodine for all consumers, especially vegetarians and vegans [16,17,42]. However, the suitability of this type of product as a matrix for food enrichment may be determined by factors influencing the stability of iodine [43][44][45]. The complexity of iodine fortification encompasses the choice of the chemical form of the compound and the optimum time and hydration [28] of the matrix.…”
Section: Introductionmentioning
confidence: 99%